Optimal Operation of Smart Houses by a Real-time Rolling Horizon Algorithm - Paterakis, Nikolaos G.; Pappi, Iliana N.; Catalao, Joao P. S.; Erdinc, Ozan (IEEE, 2016)
In this paper, a novel real-time rolling horizon optimization framework for the optimal operation of a smart household is presented. A home energy management system (HEMS) model based on mixed-integer linear programming (MILP) is developed in order to minimize the energy procurement cost considering that the household is enrolled in a dynamic pricing tariff scheme. Several assets such as a photovoltaic (PV) installation, an electric vehicle (EV) and controllable appliances are considered. Additionally, the energy from the PV and the EV can be used either to satisfy the household demand or can be sold back to the grid. The uncertainty of the PV production is estimated using time-series models and performing forecasts on a rolling basis. Also, appropriate distribution is used in order to model the uncertainty related to the EV. Besides, several parameters can be updated in real-time in order to reflect changes in demand and consider the end-user's preferences. The optimization algorithm is executed on a regular basis in order to improve the results against uncertainty.
Keywords: demand response; energy management systems; electric vehicle; photovoltaics; real-time pricing; real-time optimization; rolling optimization; uncertainty; Energy & Fuels; Engineering